2006
DOI: 10.1016/j.bbrc.2006.01.058
|View full text |Cite
|
Sign up to set email alerts
|

Differential gene dosage effects of Ad4BP/SF-1 on target tissue development

Abstract: Ad4BP/SF-1 (NR5A1) was identified as a key regulator of the hypothalamus-pituitary-gonadal and -adrenal axes. Loss-of-function studies revealed that Ad4BP/SF-1 is essential for the development of these tissues and spleen. Here, we generated transgenic mouse with BAC recombinants carrying a dual promoter and Tet-off system. These recombinants have a potential to express lacZ and Ad4BP/SF-1 in the tissues where endogenous Ad4BP/SF-1 is expressed. However, protein level of Ad4BP/SF-1 varied among the tissues of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
13
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(17 citation statements)
references
References 30 publications
4
13
0
Order By: Relevance
“…This indicates that adrenal development is more sensitive to Sf-1 dosage than gonadal development in mouse. Consistent with this, transgenic overexpression of Sf-1 rescued the gonad but not the adrenal defect in Sf-1 -/-mice, although the transgenic constructs were expressed in both tissues in wild-type animals (Fatchiyah et al, 2006). Therefore, our data strongly suggest that Sf-1 dosage has to reach a critical threshold in the AGP to trigger adrenal development and that Cited2 is required to raise Sf-1 expression above this threshold.…”
Section: Discussionsupporting
confidence: 83%
“…This indicates that adrenal development is more sensitive to Sf-1 dosage than gonadal development in mouse. Consistent with this, transgenic overexpression of Sf-1 rescued the gonad but not the adrenal defect in Sf-1 -/-mice, although the transgenic constructs were expressed in both tissues in wild-type animals (Fatchiyah et al, 2006). Therefore, our data strongly suggest that Sf-1 dosage has to reach a critical threshold in the AGP to trigger adrenal development and that Cited2 is required to raise Sf-1 expression above this threshold.…”
Section: Discussionsupporting
confidence: 83%
“…However, a more predominant dosage-sensitive effect of SF-1 on adrenal rather than gonadal formation has been suggested from a finding of the predominant reduction of adrenal size in heterozygous SF-1 KO mice [52]. A similar finding has recently been reported in an experiment that Ad4BP/SF-1 transgenic mice harboring varied expression levels of SF-1 among tissues were applied to rescue homozygous Ad4BP/SF-1 KO mice; the transgenic mice failed to rescue the adrenal gland, but successfully rescued the gonad and spleen [53]. Therefore, one approach to direct the steroidogenic cell lineage might be to control Ad4BP/SF-1 expression levels or Ad4BP/SF-1 transcriptional activity in BMC cells.…”
Section: Discussionsupporting
confidence: 67%
“…This suggested that adrenal development in mouse was more sensitive to decreased Sf-1 dosage than gonadal development. Consistent with this, forced transgenic expression of Sf-1 in Sf-1 mutant mice rescued gonad development but not adrenal development, even though the transgene was expressed in both tissues in control animals [47]. In our experiments, Sf-1 expression levels in the E10.5 AGP correlated with the severity of the adrenal phenotype.…”
Section: Cited2 Wt1 and Sf-1 Dosagesupporting
confidence: 87%